(untitled) (Scientific journal of the Fergana State University, 2025)
The article describes the improvement of the teaching of physical education in general secondary schools using the example of basketball. The article analyzes the role of basketball in the educational process, its importance in developing not only physical abilities, but also mental and social skills. Also, the role of basketball in the development of physical activity, balance, teamwork and leadership skills in students was analyzed. The article aims to show the importance of more effective teaching of physical education in the general education system and the use of basketball in the course of lessons.